Maternal methylenetetrahydrofolate reductase (MTHFR) gene A1298C polymorphism and risk of nonsyndromic Cleft lip and/or Palate (NSCL/P) in offspring: A meta-analysis - Rai, Vandana (Asian Journal of Medical Sciences, 2014)
Objective: Methyleneterahydrofolate reductase (MTHFR) A1298C polymorphism has been reported a risk factor for nonsyndromic cleft/palate (NSCL/P) in several published articles but results were inconclusive. To confirm the association between maternal MTHFR A1298C polymorphism and NSCL/P risk, a meta-analysis was conducted. Method: Case control articles for maternal MTHFR A1298C polymorphism and NSCL/P risk were identified by search of databases including PubMed, Google Scholar, Elsevier and Springer Link for the period up to December, 2013. Odds ratios (ORs) with 95% confidence intervals (CIs) were estimated to assess the association. Results: Meta-analysis of ten included studies showed that there was no significant association between maternal MTHFR A1298C polymorphism and risk of NSCL/P under five genetic models (for C versus A, OR= 1.007, 95 % CI= 0.89-1.13, P=0.90; for CC versus AA, OR=0.851, 95 % CI = 0.63-1.15, P=0.30.; for AC versus AA, OR= 1.033, 95 % CI= 0.88-1.21, P= 0.69; for CC+AC versus AA, OR= 1.005, 95 % CI= 0.86-1.17, P=0.94; for CC versus AC+AA, OR= 0.86, 95 % CI= 0.64-1.15, P= 0.32). Conclusion: In conclusion, results of present meta-analysis demonstrate that maternal MTHFR A1298C polymorphism may not be a risk factor for developing NSCL/P in offspring. Further studies with large sample sizes are needed to evaluate the association of maternal MTHFR A1298C polymorphism with NSCL/P in more detail. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10281 Asian Journal of Medical Sciences Vol.6(1) 2015 16-21